Karakterisasi fisikokimia cookies tepung sorgum termodifikasi dengan penambahan tepung kacang merah dan rosemary - Pepita Haryanti; Dwita Nafila; Nur Aini (AGROINTEK, 2026)
The development of cookies based on modified sorghum flour as a functional product has the potential to fulfill snack needs. The addition of kidney beans aims to increase the protein content and functional properties of cookies. The addition of rosemary is used as an alternative ingredient which is potent to produce of high antioxidant cookies. This study aimed to: (1) determine the best cookies formulation based on combination of red bean flour and  rosemary (puree or filtrate); (2) to identify the characteristics of the best cookies formulation containing red bean flour and rosemary. This study used a non-factorial completely randomized design (CRD). The factors studied included variations in the type of rosemary added, including filtrate and puree, in the production of red bean sorghum cookies. The parameters measured included physicochemical and sensory characterization of the cookies. The sensory characterization of the best cookies was then followed by physicochemical characterization between the best cookies and the control, including proximate analysis, color, and texture. Sorghum flour cookies with added rosemary puree and red bean flour have the same baking loss, spread ratio and moisture content values as sorghum flour cookies with added rosemary puree or filtrate. The best cookie characteristics were obtained from the formulation containing 30% red bean flour and 0.2% rosemary puree. The optimal cookies had a moisture content of 4.68%, ash content of 0.59%, protein content of 5.87%, fat content of 29.45%, carbohydrate content of 59.42%, hardness of 88.81, fracture value of 8.54, cohesiveness of 0.52, adhesiveness of 0.03, lightness (L*) of 53.16, redness (a*) of 9.21, and yellowness (b*) of 23.86. These results indicate that cookies enriched with rosemary puree and red bean flour can serve as a potential functional food alternative, offering high antioxidant activity and protein content.